The Role of Meaningfulness & Aesthetics in Increasing Revisit Intention with the Theory of Planned Behavior Approach - Muhammad Zulfi Manhaj Nujumil Ihsan; Yadi Ernawadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of hedonism, meaningfulness, and aesthetics on the revisit intention of tourists at Sabda Alam Water Park through attitude toward behavior, subjective norm, and perceived behavioral control. This study used a survey method involving 161 respondents who had experience visiting Sabda Alam Water Park. The data analysis technique used was structural equation modeling (SEM) using smartPLS software version 3.0. Based on the results of hypothesis testing, it was found that revisit intention was influenced by meaningfulness and aesthetics through attitude toward behavior. Then, it was found that meaningfulness was an antecedent of revisit intention through subjective norm, and subjective norm also had a positive effect on revisit intention through perceived behavioral control. The novelty of this study is the addition of the core constructs of TPB, namely attitude toward behavior, subjective norm, and perceived behavioral control, which are hypothesized to mediate the relationship between the dimensions of memorable tourism with the dimensions of hedonism, meaningfulness, and aesthetics on revisit intention. The researchers hope that the findings obtained can contribute to future researchers and managers of Sabda Alam Water Park in designing strategies that can increase tourists' revisit intention.